2021
DOI: 10.1111/ecog.05593
|View full text |Cite
|
Sign up to set email alerts
|

Warming threatens habitat suitability and breeding occupancy of rear‐edge alpine bird specialists

Abstract: Alpine ecosystems are particularly vulnerable to climate change. For widely distributed alpine specialists, rear‐edge populations are disproportionately important; it is expected that climate change will reduce their occupancy ranges due to the loss of suitable habitats and connectivity among them. Using four alpine bird species inhabiting the southwestern Palearctic as models, we aim to study which and how environmental factors influence habitat suitability, identify mountain areas with suitable habitat, esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 93 publications
(91 reference statements)
2
19
0
Order By: Relevance
“…This often results also in patchily distributions of species that are strictly connected to very specific elevation ranges, and also in high endemism levels ( Ruggiero & Hawkins, 2008 ; Cadena et al, 2012 ). Mountain ecosystems are consequently extremely valuable in terms of biodiversity and conservation ( Myers et al, 2000 ; Körner & Ohsawa, 2006 ; Boyle & Martin, 2015 ), but species specialist of those ecosystems are highly threatened by climate change ( e.g ., Goodenough & Hart, 2013 ; Brambilla et al, 2017 ; De Gabriel Hernando et al, 2021 ), because of their adaptation to local conditions ( Cheviron & Brumfield, 2012 ). Among birds, species distribution/abundance along elevational gradients have been investigated in several studies ( e.g ., Chamberlain et al, 2016 ; Frey, Hadley & Betts, 2016 ; Elsen et al, 2017 ; Jähnig et al, 2020 ), considering factors such as local climate, vegetation characteristics and topography as explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…This often results also in patchily distributions of species that are strictly connected to very specific elevation ranges, and also in high endemism levels ( Ruggiero & Hawkins, 2008 ; Cadena et al, 2012 ). Mountain ecosystems are consequently extremely valuable in terms of biodiversity and conservation ( Myers et al, 2000 ; Körner & Ohsawa, 2006 ; Boyle & Martin, 2015 ), but species specialist of those ecosystems are highly threatened by climate change ( e.g ., Goodenough & Hart, 2013 ; Brambilla et al, 2017 ; De Gabriel Hernando et al, 2021 ), because of their adaptation to local conditions ( Cheviron & Brumfield, 2012 ). Among birds, species distribution/abundance along elevational gradients have been investigated in several studies ( e.g ., Chamberlain et al, 2016 ; Frey, Hadley & Betts, 2016 ; Elsen et al, 2017 ; Jähnig et al, 2020 ), considering factors such as local climate, vegetation characteristics and topography as explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…There is striking evidence that white‐winged snowfinches are strictly associated with cold alpine environments, in terms of their distribution (Brambilla et al 2017a, 2020, Brambilla and Delgado 2020, BirdLife International 2021, de Gabriel Hernando et al 2021), foraging areas (Antor et al 1995, Brambilla et al 2017b, 2018), social behaviour (Delgado et al 2021), survival rates (Strinella et al 2020) and habitat and nest‐site selection (Heiniger 1991a, b1991b, Brambilla et al 2017b, Bettega et al 2020, Niffenegger 2021). The dependence of this species on cold environments is particularly strong during the breeding season (Brambilla et al 2019, 2017a, Resano‐Mayor et al 2019, Schano et al 2021, Alessandrini et al 2022, de Gabriel Hernando et al 2022): the breeding distribution of the species in European mountains is associated with low values of annual average temperature (Brambilla et al 2017a, 2020, 2017a, de Gabriel Hernando et al 2021), suggesting a thermal niche much narrower than that suggested by Cobos et al (2021). Similarly, during winter the species appears almost invariably tied to mountain sites above the treeline (Heiniger 1991a, Bettega et al 2020, Resano‐Mayor et al 2020, Delgado et al 2021, de Gabriel Hernando et al 2021; see also the wintering distribution according to BirdLife International 2021), with season‐specific distribution models showing how suitable areas during the cold season extend only partly to lower mountain ranges (de Gabriel Hernando et al 2021).…”
Section: A Worked Example: the Thermal Niche Of The White‐winged Snow...mentioning
confidence: 99%
“…The dependence of this species on cold environments is particularly strong during the breeding season (Brambilla et al 2019, 2017a, Resano‐Mayor et al 2019, Schano et al 2021, Alessandrini et al 2022, de Gabriel Hernando et al 2022): the breeding distribution of the species in European mountains is associated with low values of annual average temperature (Brambilla et al 2017a, 2020, 2017a, de Gabriel Hernando et al 2021), suggesting a thermal niche much narrower than that suggested by Cobos et al (2021). Similarly, during winter the species appears almost invariably tied to mountain sites above the treeline (Heiniger 1991a, Bettega et al 2020, Resano‐Mayor et al 2020, Delgado et al 2021, de Gabriel Hernando et al 2021; see also the wintering distribution according to BirdLife International 2021), with season‐specific distribution models showing how suitable areas during the cold season extend only partly to lower mountain ranges (de Gabriel Hernando et al 2021). In fact, unlike other typical alpine species like wheatears, water pipits and alpine choughs, observations in warmer areas at low elevation are extremely rare despite the potential suitability of habitat (Knaus et al 2018) and are more likely to occur in the case of prolonged, exceptionally cold or snowy periods and mostly linked to food shortage at higher elevation (Cramp and Perrins 1994, Glutz von Blotzheim and Bauer 1997).…”
Section: A Worked Example: the Thermal Niche Of The White‐winged Snow...mentioning
confidence: 99%
“…The increase of anthropogenic and environmental pressures, both being intimately bound, represents an unprecedented threat for vulnerable species. In particular, populations from species of high‐mountain ecosystems might not be able to move upward rapidly enough to keep within their thermal tolerances and might be doomed on their “sky islands” (see McCormack et al, 2009, e.g., De Gabriel Hernando et al, 2021, Kidane et al, 2019). Thus, species endemic to specific mountain ranges represent a major conservation issue, if only for their heritage interest.…”
Section: Introductionmentioning
confidence: 99%